Effect of pre-heating on microwave enhanced advanced oxidation process. Issue 1 (27th February 2015) - Nkansah-Boadu, Frank; Srinivasan, Asha; Liao, Ping Huang; Lo, Kwang Victor
Abstract : Aerobic sewage sludge and dairy manure were pre-treated by conventional heating (CH) (40, 50 and 60°C) followed by microwave enhanced advanced oxidation process (MW/H2 O2 -AOP) at 100 and 120°C for solids disintegration and nutrient release. Increasing CH and MW temperatures resulted in an increase in soluble chemical oxygen demand concentration and volatile fatty acids in the treated solution. The maximum ratio of soluble to total chemical oxygen demand obtained for sewage sludge and dairy manure was 60% and 22%, respectively. The synergistic effect of microwave irradiation and hydrogen peroxide (H2 O2 ) was more pronounced for sewage sludge at high CH and MW temperatures. Temperature and treatment time played a significant role in releasing orthophosphates. A maximum orthophosphate-to-total phosphate ratio of 55% and 85% was obtained for sewage sludge and dairy manure, respectively. A simple energy balance reveals that the CH step proves to be advantageous during continuous real-time operation of MW/H2 O2 -AOP technology.